Pardo: uma identidade construída no limbo? processos de subjetivação dos pardos no contexto brasileiro - ROCHA , Hortência Sousa (2023)
Faced with the complexity of the brown category, which, among its various meanings, refers to a condition “neither black nor white”, that is, to a non-place, to a kind of limbo, this research started from the following question “How do people who identify as brown deal with this non-place and what places do they build for themselves?”. In this sense, this work sought to investigate the processes of subjectivation and production of brown identities in the context of ethnic-racial relations in Brazil. To this end, three specific objectives were pursued: 1) Discuss the psychosocial implications on the construction of the identity of people who identify themselves as brown from the historicity of racial policies: whitening ideology, racial democracy and affirmative actions; 2) Knowing the experience of people who identify themselves as brown as racialized subjects in the context of Brazilian ethnic-racial relations; and 3) Analyzing how people who identify themselves as mixed race articulate in the anti-racist struggle. The research took place online and was divided into two phases: the first consisted of applying an online questionnaire, with the purpose of selection; and in the second, the semi-structured interview script was applied via video call. Eight participants were selected, of which only six composed the analyses. The interviews were analyzed using Thematic Analysis (TA). As a result, the research pointed out some aspects that mark the identification process of the interviewed subjects, such as the conflict between self-identification and racial hetero-identification, the way they perceive racial discrimination as more subtle and contextual, experiencing it in an ambiguous way, although they recognize that their bodies are racialized. In addition, some interviewees claimed a place in the middle, building a brown or mestizo identity for themselves. Furthermore, participation in the anti-racist struggle was different for each interviewee.